Legal frameworks entrepreneurship projects in Saudi Arabia - Elshite, Enas Mohammed Ebrahim; Mohamed, Roweda Musa Abdelaziz; Ahmed, Rasheeda Mahmoud Said; Sleem, Nagwa Wafa’y Mohammed (Journal of Economic, Administrative and Legal Sciences, 2023)
Entrepreneurship projects have received wide attention in the Kingdom of Saudi Arabia due to its adoption in the process of economic and social development in the country, and from this standpoint it has made full efforts to make these projects a success in accordance with the national transformation policy pursued by the Kingdom through Vision 2030, which among its objectives is the advancement of projects to support the country economically and socially which prompted it to bring about a legislative renaissance to regulate this sector, whether by drafting new legislative systems or creating existing ones in order to develop this sector in accordance with developmental policies pursued by the Kingdom that led to the development of the projects sector, despite the presence of challenges that impede the policies pursued by the state to achieve the desired objectives, and accordingly, this study came, which contains a statement of the nature of projects and the concept of entrepreneurship with the study and analysis of the legal frameworks for these projects, and an indication of the development policies on which the Kingdom relied in its plan and the challenges facing these projects, as the researcher concluded through the study that the Kingdom witnessed legislative reforms in order to promote entrepreneurship projects that have positively affected the economy and its contribution to development process.